2020
DOI: 10.32479/ijeep.9783
|View full text |Cite
|
Sign up to set email alerts
|

The Lead Lag Relationship Between Spot and Futures Markets in the Energy Sector: Empirical Evidence From Indian Markets

Abstract: The study aims at finding the intraday Lead-Lag relationship between Spot and Futures Market for Energy Sectors Stocks on which Single Stock Futures (SSFs) is available, by applying 1-min Price Returns for the period ranging from April 1, 2017 to March 31, 2019. The study explores pricediscovery between stock futures and their underlying stocks by applying vector error correction model, Hasbrouck (1995) Information Shares, and Common Factor Component Weights of Gonzalo and Granger (1995). The findings indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
3
2
0
Order By: Relevance
“…In summary, the results of the TOP method show that the futures and options exhibit price leadership over the spot market, and the options is ahead of the futures on most trading days in the Chinese mainland market, which are generally in line with the results in Hong Kong and US markets. These conclusions are consistent with Ren et al ( 2019 ), Ahn et al ( 2019 ) and Raju and Shirodkar ( 2020 ).…”
Section: Data and Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In summary, the results of the TOP method show that the futures and options exhibit price leadership over the spot market, and the options is ahead of the futures on most trading days in the Chinese mainland market, which are generally in line with the results in Hong Kong and US markets. These conclusions are consistent with Ren et al ( 2019 ), Ahn et al ( 2019 ) and Raju and Shirodkar ( 2020 ).…”
Section: Data and Resultssupporting
confidence: 92%
“…In summary, inconsistent with the Efficient Markets Hypothesis (Fama, 1991 ; Shao et al., 2019 ), our research based on high-frequency data suggests that the futures and options exhibit price leadership over the spot market, and the options is ahead of the futures on most trading days in all three markets. These findings complement the work (Ren et al, 2019 ; Ahn et al 2019 ; Raju & Shirodkar, 2020 ) on the dynamic variation of intraday lead–lag relations between the index and its derivatives. In addition, there is a reversal phenomenon of the relation between the derivative and its underlying index, which is different from previous studies and enriches the empirical research in this area.…”
Section: Data and Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Raju and Shirodkar (2020) [18] have investigated the lead-lag relationship between the spot and futures markets of energy sector stocks on which single stock futures (SSFs) are available and found that future markets leads in price discovery process. Zavadska et al (2018) [21] analyzed the behavior and importance of crude oil in the global economy with a more focus on investigating the lead-lag relationship between the spot and future markets.…”
Section: Literature Reviewmentioning
confidence: 99%